2021
DOI: 10.1158/1078-0432.ccr-21-2007
|View full text |Cite
|
Sign up to set email alerts
|

Results from Phase I Extension Study Assessing Pexidartinib Treatment in Six Cohorts with Solid Tumors including TGCT, and Abnormal CSF1 Transcripts in TGCT

Abstract: Purpose: To assess the response to pexidartinib treatment in six cohorts of adult patients with advanced, incurable solid tumors associated with colony-stimulating factor 1 receptor (CSF1R) and/or KIT proto-oncogene receptor tyrosine kinase activity. Patients and Methods: From this two-part phase I, multicenter study, pexidartinib, a small-molecule tyrosine kinase inhibitor that targets CSF1R, KIT, and FMS-like tyrosine kinas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…In this case 20% of the reads show a splice variant that lacks the exon 6 transmembrane domain (data not shown). The sequences from CSF1 translocations reported by Tap et al (6) also point to the loss of the CSF1 transmembrane domain and cleavage site but also the potential gain of other transmembrane domains from the translocation partners, for example in the translocations involving CD99 and CD101 as fusion partners. The presence of the membrane bound CSF1 could explain the advantage of a dendritic morphology in the neoplastic cells to facilitate interaction with the macrophages and further studies are required to address this issue.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…In this case 20% of the reads show a splice variant that lacks the exon 6 transmembrane domain (data not shown). The sequences from CSF1 translocations reported by Tap et al (6) also point to the loss of the CSF1 transmembrane domain and cleavage site but also the potential gain of other transmembrane domains from the translocation partners, for example in the translocations involving CD99 and CD101 as fusion partners. The presence of the membrane bound CSF1 could explain the advantage of a dendritic morphology in the neoplastic cells to facilitate interaction with the macrophages and further studies are required to address this issue.…”
Section: Discussionmentioning
confidence: 91%
“…These cells attract and stimulate a large population of bystander macrophages (3). A number of studies have shown that these tumors react to inhibition of the CSF1 pathway (6)(7)(8)(9)(10)(11)(12)(13)24). To better understand the "landscaping effect" caused by the neoplastic cells on the tumor micro environment we used scRNA-seq and long read RNA-seq.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations